Training to Improve Customer Satisfaction through Product Quality Enhancement - El Hakim, Muhammad Luqman; Maidalena, Maidalena; Erlangga, Muhammad Rizky (Universitas Islam Negeri Sumatera Utara, 2024)
Technological advancements, including those in telecommunications, are rapidly evolving, and mobile phones have become essential tools for various activities, supported by prepaid cards for communication and internet use. In Indonesia, with a population of approximately 261 million and around 231 million mobile phone users, the demand for reliable telecommunication services is significant. Telkomsel, a major telecommunications provider in Indonesia, plays a pivotal role in this sector. Despite high product quality, Telkomsel faces the challenge of maintaining and enhancing customer satisfaction amid rising competition. This study investigates how improving product quality can impact customer satisfaction, focusing on Telkomsel’s internet service packages. Using methods such as Coaching and Deep Interviews with students from the State Islamic University of North Sumatra, the research identifies key strategies for enhancing service quality. Results indicate that consistent service quality, competitive pricing, customer feedback integration, and responsive customer service are crucial for maintaining customer loyalty. The study concludes that Telkomsel must continuously improve its service quality to meet evolving consumer expectations and remain competitive.